Effect Of Vêo® Premium and Vitamin C Supplementation on Lipid Profile Before and During Pregnancy in Some Local Iraqi Ewes During Heat Stress - Alani, Othman Ghazi Najeeb; Abdul-Rahaman, Yassen Taha; Mohammed, Thafer Thabit (Iraqi Journal of Science, 2021)
The present study was designed to investigate the effects of VêO® premium and vitamin C (Vit. C) supplementation on lipid profile before and during pregnancy in local Iraqi ewes during heat stress. The study was conducted in a private field in Fallujah city, west Iraq, during the period from 6/8/2019 to 8/2/2020. Twenty local Iraqi ewes were divided randomly into four equal groups (5 for each group) The first group (T1) was given VêO® premium (4 g/ ewe/ day), the second group (T2) was given VêO® premium (2 g/ ewe/ day), and the third group (T3) was given Vit. C (40 mg/ ewe/ day), and the fourth group (T4) was left without treatment, as a control group. After 14 days of treatment, vaginal sponges were inserted for 14 days and, after their withdrawal, the rams were introduced for 6 days. Blood samples were collected from the jugular vein into vacutainer tubes (10 ml) at 4 periods (periods 1 and 2 before pregnancy; periods 3 and 4 during pregnancy). Lipid profile parameters were also estimated, which includes cholesterol, triglyceride, high density lipoprotein (HDL), low density lipoprotein (LDL), very low density lipoprotein (VLDL), and malondialdehyde (MDA). There were no significant difference in the serum levels of cholesterol, triglyceride, HDL, and LDL among the various treatments before and during pregnancy. The level of VLDL was significantly higher in T2 group as compared to the other treatments (P≤0.05) at the fourth periods. There was a significant difference in the level of MDA (P≤0.05) in treatment T3 in the first period compared with the treatments T1, T2, and T4, whereas treatment T4 showed significantly higher level (P≤0.05) in the second, third, and fourth periods as compared to treatments T1, T2, and T3. In conclusion, different effects of VêO® premium and Vitamin C supplementation were noticed on the lipid profile before and during pregnancy in local Iraqi ewes during heat stress.